Docker cookbook : over 100 practical and insightful recipes to build distributed applications with Docker /: over 100 practical and insightful recipes to build distributed applications with Docker. (2018) - Cochrane, Ken; Chelladhurai, Jeeva S; Khare, Neependra
No abstract available